Asthma and allergic rhinitis risk depends on house dust mite specific IgE levels in PARIS birth cohort children() - Gabet, Stephan (World Allergy Organ J, 2019)
BACKGROUND: The natural history of allergic sensitization in childhood, and its impact on allergic disease development, needs to be clarified. This study aims to identify allergic sensitization and morbidity patterns during the first 8 years of life. METHODS: The study was conducted in the on-going population-based prospective Pollution and Asthma Risk: an Infant Study (PARIS) birth cohort. Sensitization profiles were identified by k-means clustering based upon allergen-specific IgE levels measured at 18 months and 8/9 years. Allergic morbidity profiles were identified by latent class analysis based on symptoms, symptom severity, treatments, and lifetime doctor-diagnoses of asthma, allergic rhinitis, and atopic dermatitis and on lower respiratory infections before 2 years. RESULTS: Five sensitization and 5 allergic morbidity patterns were established in 714 children. Children not sensitized or with isolated and low allergen-specific sensitization were grouped together (76.8%). A profile of early and transient sensitization to foods that increased the risk of asthma later in childhood was identified (4.9%). Children strongly sensitized (≥3.5 kU(A)/L) to house dust mite at 8/9 years (9.0%) had the highest risk of asthma and allergic rhinitis. Finally, timothy grass pollen at 8/9 years sensitization profile (5.3%) was related to respiratory allergic diseases, as was early onset and persistent sensitization profile (4.1%), this latter being also strongly associated with atopic dermatitis. CONCLUSIONS & CLINICAL RELEVANCE: We show that accurate assessment of the risk of allergic disease should rely on earliness and multiplicity of sensitization, involved allergens, and allergen-specific IgE levels, and not considering solely allergic sensitization as a dichotomous variable (allergen-specific IgE ≥0.35 kU(A)/L), as usually done. This is particularly striking for house dust mite. We are hopeful that, pending further confirmation in other populations, our findings will improve clinical practice as part of an approach to allergic disease prevention.